ARCHITECTURE OF LOWER OLIGOCENE SOURCE ROCKS IN THE ALPINE FORELAND BASIN: A MODEL FOR SYN- AND POST-DEPOSITIONAL SOURCE-ROCK FEATURES IN THE PARATETHYAN REALM - Sachsenhofer R.F.; Schulz H.-M. (My University, 2006)
Oligocene rocks are one of the most important sources of hydrocarbons within the Paratethyan realm. In the Alpine Foreland Basin (Central Paratethys) the main Oligocene source rock is the Schöneck Formation, but organic-rich rocks occur in the entire Lower Oligocene succession. Based on well-log calibration by core data, the spatial distribution and thickness variations of different Lower Oligocene source-rock facies are investigated. The deeper-water sediments are characterized by lateral continuity, but exhibit vertical variability. The latter reflects major palaeoceanographic changes in the Central Paratethys, such as the closure of seaways, basin-wide changes in salinity and in redox conditions. The upper shaly part of the Schöneck Formation has the highest source potential (>5% TOC, initial HI: 500-600 mgHC g-1 TOC) and reaches its maximum thickness (c. 5 m) in a narrow belt parallel to the palaeo-shoreline. The present-day distribution of Lower Oligocene rocks is controlled by submarine erosion which affected the northern passive slope of the foreland basin. Erosion climaxed during the late Early Oligocene. The eroded material was re-deposited along the lower basin slope (Oberhofen facies). The source-rock potential of the re-deposited sediments is relatively low. The oil kitchen (4-7 km burial depth) is located beneath the Alpine nappes where the Lower Oligocene succession was removed locally by the advancing nappes. Both submarine erosion at the northern basin slope and tectonic erosion beneath the Alps have to be considered in the evaluation of the prospectivity of the basin. Because deposition of the Lower Oligocene succession in the Alpine Foreland Basin is controlled by basin-wide processes, it may serve as a model for source-rock deposition in foreland basins of the Paratethyan realm (e.g. Carpathians, Terek-Caspian Foredeep). © 2006 EAGE/Geological Society of London.
Keywords: LOG FACIES; MOLASSE BASIN; OLIGOCENE; PARATETHYS; SOURCE ROCK; Cenozoic::Paleogene::Oligocene; Кайнозой::Палеоген::Олигоцен